2011
DOI: 10.1111/j.1757-837x.2011.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical damage to navy beans as affected by moisture content, impact velocity and seed orientation

Abstract: Introduction Mechanical damage of seeds due to harvest, handling and other process is an important factor that affects the quality of seeds. Objectives To evaluate the impact damage to navy bean seeds. Methods The study was conducted under laboratory conditions, using an impact damage assessment device. Independent variables were: seed moisture content (10, 12.5, 15, 17.5, 20, and 25% wet basis), impact velocity (5, 7.5, 10, 12.5, and 15 m/s) and seed orientation (side and end). Results Impact velocity, moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…Similar results regarding seed damage due to impact energy have been reported by Shahbazi et al. () for pinto beans and Shahbazi et al. () for cowpea seeds.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results regarding seed damage due to impact energy have been reported by Shahbazi et al. () for pinto beans and Shahbazi et al. () for cowpea seeds.…”
Section: Resultssupporting
confidence: 89%
“…(), on pinto bean by Shahbazi et al. () and on cowpea seeds by Shahbazi, Dolatshah, and Valizadeh ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical damage of seeds is also an important factor that affects the quality of seeds (Shahbazi et al, 2011). Seed damage results in lower grain value, problems with storage, and reduces seed germination and seedling vigor and subsequent reduction in crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…Seed damage results in lower grain value, problems with storage, and reduces seed germination and seedling vigor and subsequent reduction in crop yield. Shahbazi et al (2011) conducted tests to determine the extent of damage due to impact on percent physical damage (PPD) and percentage germination loss (PLG) (physiological damage) of pinto beans. The results indicated that two independent variables, moisture content and impact energy, significantly influenced the PPD, PLG and total damage of pinto bean seeds (Shahbazi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%